Simulation based distracted driver detection system using alcohol sensor and fusion of bioelectric signals to disseminate them through V2V/V2I to alleviate risky driving - Sikder, Md. Sarfaraj; Ashary, Abu Musa; Ahmed, Nahid; Mahfuz, Soud Ibne (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.